1997
DOI: 10.1074/jbc.272.11.6835
|View full text |Cite
|
Sign up to set email alerts
|

Both p140 and p75NGFR Nerve Growth Factor Receptors Mediate Nerve Growth Factor-stimulated Calcium Uptake

Abstract: Human p140trk and p75 NGFR were transfected separately into 3T3 cells. Nerve growth factor stimulates calcium uptake into both transfectants but not into untransfected 3T3 cells. p140 trk cells were stimulated maximally by 25 ng/ml; 100 ng/ml was submaximal for p75 NGFR cells. K-252a inhibits the effect of NGF on p140 trk cells but not on p75 NGFR cells; brain-derived neurotrophic factor stimulates calcium uptake in p75 NGFR cells but not in p140 trk cells. The data suggest that both nerve growth factor recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…However, some reports have indicated that NGF and EGF are able to induce a small and rapid increase in [Ca 2ϩ ] i (57,65,80,92; reviewed in reference 47). More recent results have reported that NGF-induced increases in [Ca 2ϩ ] i seem to arise from both intracellular stores and extracellular spaces being mediated by the Trk receptor (16,48,75). However, in those reports, the functional relevance of Ca 2ϩ mobilization after NGF stimulation was not clear.…”
Section: Discussionmentioning
confidence: 75%
“…However, some reports have indicated that NGF and EGF are able to induce a small and rapid increase in [Ca 2ϩ ] i (57,65,80,92; reviewed in reference 47). More recent results have reported that NGF-induced increases in [Ca 2ϩ ] i seem to arise from both intracellular stores and extracellular spaces being mediated by the Trk receptor (16,48,75). However, in those reports, the functional relevance of Ca 2ϩ mobilization after NGF stimulation was not clear.…”
Section: Discussionmentioning
confidence: 75%
“…The pCMV-trkA expression plasmid (36) and the pCMV5-p75 expression plasmid (kindly provided by Dr. Moses Chao) were transfected separately into NIH 3T3 cells by the calcium phosphate method as described previously (36). The stable clones WT11, L2, and L9 were selected in 0.5 mg/ml G418 and were used in the present studies.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study it was shown that NGF induced an increased uptake of calcium into 3T3 cells stably transfected with either p140 trk or p75 NGFR (36). In the present study we used confocal microscopy to investigate further the alterations in calcium levels produced by NGF in these two separate cell populations.…”
mentioning
confidence: 99%
“…NGF can mediate increases in cytoplasmic C a 2ϩ concentration (De Bernardi et al, 1996;Jian et al, 1997). Therefore, we investigated the involvement of cytoplasmic [C a 2ϩ ] in the induction of filopodial sprouts by NGF-coated beads.…”
Section: Role Of Ca 2ϩ Fluxesmentioning
confidence: 99%